Carbon quantum dots decorated N-doped ZnO: Synthesis and enhanced photocatalytic activity on UV, visible and daylight sources with suppressed photocorrosion. Issue 1 (March 2016) - Muthulingam, S.; Bae, Kang Bin; Khan, Rizwan; Lee, In-Hwan; Uthirakumar, Periyayya
Graphical abstract: Highly efficient and eco-friendly CQD/N-ZnO composite exhibits an improved photocatalytic activity under different light sources. Highlights: The CQD/N-ZnO composites were prepared by a simple one step method. An improved photocatalytic activities on MG dye under different light. Suitable for treating huge volume of wastewater in industry. Abstract: Carbon quantum dots decorated N-doped ZnO (CQD/N-ZnO) composites were prepared by a simple one step method. The existence of CQD and ZnO phases in the CQD/N-ZnO composite was confirmed by XRD, Raman, XPS and HRTEM techniques. The CQD/N-ZnO composite exhibited an enhanced photocatalytic performance on aqueous malachite green dye, irrespective to the light sources of UV, visible and daylight. The dye degradation of ∼38% and 99% was noticed for N-doped ZnO and CQD/N-ZnO photocatalyst, respectively after 15 min of daylight irradiation and it required just 30 min to degrade an entire dye. Repeated photocatalytic experiment was carried out to investigate the reusing capability of CQD/N-ZnO photocatalyst and it was found that the suppressed photocorrosion offered by CQDs coverage on the ZnO crystals.